Effectiveness of High-Velocity Low-Amplitude Manipulation in the Treatment of Ankle Joint Dysfunction: A Comprehensive Review - Roberto Tedeschi (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Ankle joint manipulation is a commonly used intervention in orthopedic and rehabilitation settings. Its efficacy in improving the range of motion, reducing pain, and enhancing functional performance is a subject of ongoing research.